Characterizing the bending behavior of underground utility tunnel roofs in a fabricated composite shell system - Dong, Lei; Yao, Aijun; Zhou, Daxing; Zhang, Pengfei (Frontiers in Materials, 2023)
This study proposes a new fabricated underground utility tunnel system — underground utility tunnels in the fabricated composite shell system. As the permanent formwork, 20 mm thick high-performance cement-based material is used, and the framework of steel reinforcement is located in the cavity between the formwork shells on both sides. After the on-site hoisting is performed in place, concrete is poured to form integral tunnels. This research investigates the system design, clarifies the system's component structure and connection structure, and evaluates the mechanical properties of high-performance cement-based material used in the formwork shells. A bending test is conducted on the roof specimen of utility tunnels in the composite shell system. The test results indicated that the roof specimen of the composite shell system presents the same failure phenomenon as the cast-in-place roof specimen, and their bearing capacity, stiffness, and others are identical to those of the cast-in-place structures. Based on the analysis of the experimental phenomena and results, the characteristics of the formwork material, and the bending test outcomes, a formula for calculating the roof's bearing capacity in a composite shell system is proposed. The calculated results agree well with the experimental values.